Techno-Economic Analysis of Sawdust-Based Trash Cans and Their Contribution to Indonesia’s Green Tourism Policy and the Sustainable Development Goals (SDGs) - Afmi Apriliani; Cecep Waahyudin; Faisal Tri Ramdani; Abraham Yazdi Martin; Dede Syahrudin; Denny Hernawan; Euis Salbiah (Bumi Publikasi Nusantara, 2026)
This study investigated the techno-economic feasibility of producing trash cans from sawdust waste to support sustainable waste management and smart tourism infrastructure in Indonesia. With the growing volume of tourist-generated waste and increasing demand for eco-friendly public facilities, this innovation offers a low-cost, circular economy solution. A 20-year financial projection was conducted using indicators such as Net Present Value (NPV), Gross Profit Margin (GPM), Payback Period (PBP), and Return on Investment (ROI). Results indicate strong economic viability, with an initial investment of USD 19,500 and a payback period of just over two years. The model contributes to SDG 11 (Sustainable Cities and Communities) and SDG 12 (Responsible Consumption and Production), and aligns with national policy frameworks such as RIPPARNAS, RPJMN, and Ministerial Regulation No. P.75/MENLHK/2019. This study presents a scalable solution for local governments and tourism authorities to enhance environmental infrastructure while promoting sustainability and community-driven innovation in tourism destinations.This study investigated the techno-economic feasibility of producing trash cans from sawdust waste to support sustainable waste management and smart tourism infrastructure in Indonesia. With the growing volume of tourist-generated waste and increasing demand for eco-friendly public facilities, this innovation offers a low-cost, circular economy solution. A 20-year financial projection was conducted using indicators such as Net Present Value (NPV), Gross Profit Margin (GPM), Payback Period (PBP), and Return on Investment (ROI). Results indicate strong economic viability, with an initial investment of USD 19,500 and a payback period of just over two years. The model contributes to SDG 11 (Sustainable Cities and Communities) and SDG 12 (Responsible Consumption and Production), and aligns with national policy frameworks such as RIPPARNAS, RPJMN, and Ministerial Regulation No. P.75/MENLHK/2019. This study presents a scalable solution for local governments and tourism authorities to enhance environmental infrastructure while promoting sustainability and community-driven innovation in tourism destinations. © 2026 Bumi Publikasi Nusantara